The Evaluation of Full Day School Program in SMAN 10 Singkawang - Arianto Arianto; Sukmawati Sukmawati; Usman Radiana (STKIP Singkawang, 2018)
The objectives of this study include 1) describing and analyzing evaluations on context components which include: the development of the school's vision and mission that describes the objectives of Full Day School implementation in Singkawang 10 State Senior High School (SMAN 10 Singkawang); 2) Describe and analyze evaluations on input components which include: curriculum development, educators, administrative personnel, facilities and infrastructure as well as financing in accordance with educational standards; 3) describe and analyze evaluations on process components which include: learning process, management in accordance with educational standards; 4) describe and analyze evaluations on product components which include: UN scores and graduation for the 12th year students of the current year 2016-2018. This study uses a qualitative approach with a descriptive type of research. From the data collected at the time of the research on the Evaluation of FDS Program at SMAN 10 Singkawang, the Context, Input, Process and Product evaluation obtained the following results: 1) In the evaluation of the context, the Vision and Mission of SMAN 10 Singkawang was in accordance with education. character based and government objectives in the FDS program; 2) In the Input evaluation it was concluded that the curriculum used in SMAN 10 Singkawang still refers to the KTSP and K13 curriculum, lack of teachers and TU and the lack of facilities and infrastructure available in schools; 3) In the process evaluation includes the learning process that has been carried out according to SNP standards, the teacher makes a lesson plan (RPP) as a PBM guide and is supervised by the Principal regularly and the Principal designs the school budget by arranging the RKAS within one year from the committee funding sources and BOSS; 4) Results of discussion about the results The product evaluation includes learning outcomes during the FDS implementation at SMAN 10 Singkawang can be concluded that during the 3 years running the implementation of FDS in SMAN 10 Singkawang has not improved the quality of education (seen from the UN average score data). Still below the average 6.00 (SNP standard).